Ergonomic chair design for musculoskeletal disorder (MSD) / Norhafizah Rosman … [et al.] - Rosman, Norhafizah; Abdul Jalil, Ainul Munirah; Haroon, Fazlinarulzaiha; Kusin, Mazlin (2015)
The purpose of this study was to observe the anthropometric data collected compared to the existing data, Data was determined to propose the new design of school chair. The data collection was conducted at SK Jengka Pusat 2 located in front of UiTM Jengka, Pahang and the samples were the school students. The range of ages of the samples were around 7 to 12 years old among the students who volunteer to be physically measured in this study, The samples 125 male students and 125 female students. Thirteen human body dimensions were measured: stature, shoulder breadth, chest depth, sitting height, sitting eye height, sitting shoulder height, popliteal height, sitting kl1ee height, forearm hand length, sitting elbow height, thigh clearance, head length and hip breadth, Finally, the anthropometric data was compared to the previous study. The findings showed similarity with the existing data. Presently, designing ergonomic workstation at school becomes an important task in order to create better sitting habits for youngsters despite taking into consideration the other factors that may influence the furniture itself. This is because school children remain seated in static and poor posture throughout their lesson, usually with their chest back and neck flexed or rotated making it difficult to change the sitting habits later in adulthood.